Efeitos de degradação e de alterações microestruturais do polímero no desempenho mecânico estático de juntas híbridas de polieterimida (PEI) e alumínio produzidas por F-ICJ - Sônego, Marília (Universidade Federal de São Carlos, 2016)
This master thesis aims to study hybrid joints of polyetherimide (PEI) and aluminum 6082-T6 produced by Friction-based Injection Clinching Joining (FICJ). The influences of the process parameters in the frictional heat and polymer degradation were analyzed through a half factorial design. The degradation of PEI was evaluated by size exclusion chromatography (SEC), differential scanning calorimetry (DSC) and infrared spectroscopy (FTIR). The effect of degradation in the joint microstructure and mechanical properties was also analyzed. The macro and microstructural characteristics were evaluated by optical microscopy and Vickers hardness. The static mechanical properties were determined by lap shear testing and cross tensile testing. It has been shown that the F-ICJ causes degradation through multiple chains scissions. Additionally, a thermomechanically affected zone, with lower hardness, and defects such as pores and weld lines are formed. The mechanical performance, mainly in cross tensile testing, is negatively affected by degradation and presence of defects. These results contribute to the optimization and application of F-ICJ to join hybrid structures.
Effects of polymer degradtion and microstructural changes in the static mechanical performance of hybrid joints of polyetherimide (PEI) and aluminum produced by F-ICJ
Keywords: União por fricção; Rebitagem por injeção baseada em energia friccional; F-ICJ; Juntas híbridas; Polieterimida; PEI; Degradação; Friction joining; Injection-based clinching joining; Hybrid joints; Polyetherimide; Degradation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA